Cellular respiration and amino acid metabolism is altered by dietary oligosaccharides in Salmonella with epithelial cell association - Shaw, Claire A.; Chen, Poyin; Arabyan, Narine; Weimer, Bart C. (Frontiers in Microbiology, 2025)
IntroductionDietary prebiotic oligosaccharides, complex carbohydrates that support beneficial bacteria, are ubiquitous on marketplace shelves and in people’s diets. Though widely accessible and consumed, little is known about how different prebiotics alter the epithelium and microbes during enteric infections.MethodsHere we show two structurally different prebiotic oligosaccharides, human milk oligosaccharides (HMO) and mannanoligosaccharides (MOS), alter the metabolism of colonic epithelial cells and Salmonella enterica sv. Typhimurium in ways specific to each prebiotic during infection in a focused ‘in vitro’ model.ResultsInitially, HMO and MOS addition decreased S. Typhimurium association with epithelial cells. However, gene expression analysis revealed significantly induced expression of Specific Pathogenicity Island (SPI) 1 (adj. p < 2.0−6) and 2 (adj. p < 3.0−5) with HMO treatment, opposed to increased fimbriae expression (adj.p < 3.0−3) with MOS treatment. Both host and pathogen metabolism were likewise altered with prebiotic addition. MOS treatment induced the expression of genes for amino acid metabolism in both the host cells and in S. Typhimurium, a metabolic shift that was not observed in the HMO treated cells. MOS treatment also altered pathogen-related respiration metabolism in S. Typhimurium toward activity typically seen during gut inflammation.DiscussionThe regulation of virulence expression in Salmonella from prebiotic treatment was unexpected and suggests prebiotics act in context-dependent ways to potentiate or attenuate enteric activity.